Genomic insights into Mediterranean pepper diversity using ddRADSeq - Tuğba Pelin Toker; Damla Ulusoy; Betül Doğan; Serkan Kasapoğlu; Fidan Hakan; Umesh K. Reddy; Mojtaba Kordrostami; Engin Yol (PLoS ONE, 2025)
This work investigated the genetic diversity and population structure of 99 pepper lines (Capsicum annuum L.), acclimated to Mediterranean climate conditions, using double-digest restriction site-associated DNA sequencing (ddRADSeq). The aims were to understand the genetic relationships among these lines, correlate genetic clusters with botanical classifications, and provide insights into pepper domestication in the region. Obtained were 318.76 million raw sequence reads overall, averaging 3.21 million reads per sample. A total of 8475 high-quality SNPs were identified and used to assess genetic diversity and population structure. Chromosome NC_061113.1 displayed the highest amount and Chromosome NC_061118.1 the fewest of these SNPs, which were not equally spaced around the genome. Heterozygosity measures and a negative inbreeding coefficient point to the great genetic diversity seen, therefore highlighting the genetic health of the population. Different genetic clusters found by phylogenetic study and STRUCTURE analysis can be used in breeding programs to mix desired features from many genetic backgrounds. This work showed how well ddRADSeq generates high-quality SNPs for genomic research on peppers, therefore offering useful molecular tools for genomic selection and marker-assisted selection. The analysis identified significant genetic diversity and distinct genetic clusters which are valuable for breeding programs focused on crop improvement. These findings enhance our understanding of pepper domestication and provide valuable genetic resources for breeding programs aimed at improving pepper varieties.